Value Orientations of Journalism Students in Context of their Academic Training - Yankovska, Zhanna; Marchuk, Liudmyla; Rarytskyi, Oleh (Journal of Education Culture and Society, 2022)
Aim. To determine and analyse motivating factors, which influence the education component of forming successful Ukrainian journalist students and their value orientations. Methods. The main research methods are observation, test, interview, questionnaire and analysis of scientific works. A set of diagnostic tools was used among which were the Dmitriy Leontyev’s Purpose-in-Life Test, which included three most vital life orientations: purpose of life, its eventfulness and self-realisation, and Milton Rokeach’s Value orientations questionnaire. For processing the data, the following analysis methods were used: processing of quantitative data by applying methods of mathematical analysis of statistical; Student’s t-test to compare medians of two independent samples; Spearman’s rank correlation; processing of qualitative data: content study and analysis, processing of the obtained data; quantitative and qualitative analysis. Results. The practical value of the research results consisted in determining modern value orientations and learning and professional motivation of the successful Ukrainian student-journalists as well as finding out that the profession of a journalist can be successful. Conclusion. It was identified that journalist education has a specific character, which should include motivating students to achieving success in learning and professional development. The study demonstrated that the future professional competency growth of the journalism students can be achieved with the development of their instrumental and terminal values. Some student’s success indicators were identified for implementing in the student professional training in order to motivate them to learning and professional efficiency and forming their system of value orientations.